PENGARUH PENERAPAN MODEL PEMBELAJARAN BLENDED LEARNING TERHADAP HASIL BELAJAR KEARSIPAN SISWA KELAS X SMK AR-RAHMAN MEDAN T.A 2021-2022 - Rani Zuliani; Samio Samio (Jurnal Inovasi Penelitian, 2022)
The type of research used is quantitative research. The data collection instrument was a multiple choice test with 30 items. The sampling technique used is the saturated sampling technique. Where the entire total population is 60 people while the set sample is 28 people as the research sample. From the results of the study, the average learning outcomes using the Blended learning learning model were 87.6. Meanwhile, the results of hypothesis testing using the t-test formula obtained tcount of 1.82 while ttable was obtained for N=28 at a significant level of 0.23. By comparing tcount and ttable, it was obtained tcount ttable 1.82 0.23, which means the research hypothesis is accepted. the truth. Thus, it can be concluded that there is a significant influence between the Blended Learning learning model on archival learning outcomes in class X students of the Ar-Rahman Private Vocational School in Medan in 2021-2022. The conclusion of this study is that using the blended learning model can improve student learning outcomes.